Students' Cognitive Abilities and Self-Regulated Learning in Digital Mathematics Learning - Agus Adnan; Izoya Putri (Gema Cendekia Institute, 2026)
Advances in educational technology have encouraged the integration of digital learning into mathematics learning, so the main challenge faced is how students can optimize their cognitive abilities and self-regulated learning (SRL) in digital environments. Students' cognitive abilities—which include thinking processes, conceptual understanding, and mathematical reasoning—are key to the success of digital mathematics learning. Meanwhile, SRL, as students' ability to plan, monitor, and evaluate their own learning process, plays a crucial role in regulating the effective use of digital resources, including time management, learning strategies, and emotional regulation. This article describes the relationship between students' cognitive abilities and SRL in the context of digital mathematics learning and the factors that influence both aspects. The study results indicate that the use of digital learning technology combined with strategies to enhance SRL can improve students' conceptual understanding and mathematical problem-solving skills. The interaction between cognitive abilities and SRL also strengthens the role of metacognition in helping students learn independently and effectively in digital environments. This study proposes a learning model that combines digital features with scaffolding techniques designed to strengthen students' cognition and self-regulation to improve mathematics learning outcomes.